2021
DOI: 10.3390/ijms22041831
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Tyrosine Kinase Signaling and Targeting in Glioblastoma Multiforme

Abstract: Glioblastoma multiforme (GBM) is amongst the deadliest of human cancers, with a median survival rate of just over one year following diagnosis. Characterized by rapid proliferation and diffuse infiltration into the brain, GBM is notoriously difficult to treat, with tumor cells showing limited response to existing therapies and eventually developing resistance to these interventions. As such, there is intense interest in better understanding the molecular alterations in GBM to guide the development of more effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 312 publications
(365 reference statements)
0
43
0
Order By: Relevance
“…Recent histologic–molecular correlations have also focused on the phenotype associated with FGFR3 fusions in glioblastoma [ 7 , 23 , 24 ]. The efforts for molecularly classifying glioblastoma have been recently reviewed [ 25 ] and are based on a bioinformatics study categorizing in three different clusters the tumors with EGFR, NF1, and PDGFRA/IDH genetic alterations [ 26 ]. However, a more refined and inclusive molecular classification is warranted due to the lack of prognosis stratification for glioblastoma patients, and to the lack of efficacious specific therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent histologic–molecular correlations have also focused on the phenotype associated with FGFR3 fusions in glioblastoma [ 7 , 23 , 24 ]. The efforts for molecularly classifying glioblastoma have been recently reviewed [ 25 ] and are based on a bioinformatics study categorizing in three different clusters the tumors with EGFR, NF1, and PDGFRA/IDH genetic alterations [ 26 ]. However, a more refined and inclusive molecular classification is warranted due to the lack of prognosis stratification for glioblastoma patients, and to the lack of efficacious specific therapies.…”
Section: Discussionmentioning
confidence: 99%
“…It assigns all the glioblastoma cases to seven molecular subgroups, G1–G7, and shows their prognostic stratification. The classification was performed on a relatively large controlled cohort compared to cohorts from other studies [ 25 ]. Importantly, the cohort is representative for a mixed demographic population, including both Caucasian/White and African-American/Black ethnicities, providing thus more inclusive information than previously analyzed cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the activation of PDGFR-signaling via a PDGF-nitric oxide (NO)-ID4-regulatory circuit ( 155 ) in humans accounts for tumorigenesis in 30% of GBM patients, and the overexpression or alterations of PDGF ligands are commonly found in GBM patients, especially in a proneural subtype of GBM, which contributes to the development of GBM and the function of GSCs, such as the self-renewal and tumor-initiating capacity to different extents among PDGFRα and PDGFRβ ( 155 ). Among several PDGF inhibitors, such as imatinib, tandutinib, AG1433, and nilotinib ( 138 , 156 ), the small molecule TKI imatinib (also known as Gleevec; Glivec; STI-571) has been demonstrated to enable the growth of GBM xenografts in vivo to inhibit and the radiosensitivity of human GSCs in vitro to increase ( 157 ), but it has no significant therapeutic effect on recurrent GBM ( 156 ).…”
Section: Direct Targeting Of Gscsmentioning
confidence: 99%
“…It has also been reported that genetic alterations, such as loss or mutations in the phosphate and tensin homologue ( PTEN ) gene or overexpression of the platelet-derived growth factor receptor alpha ( PDGFRA ) gene, represent additional molecular biomarkers that may be correlated with tumor evolution and poor prognosis ( 11 , 12 ). Finally, different receptor tyrosine kinases (RTKs) and their ligands represent promising therapeutic targets for the treatment of GBM because they are involved in disease invasiveness, angiogenesis and cancer cell survival ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%